Intrathecal Drug Delivery Systems for Cancer Pain: An Analysis of a Prospective, Multicenter Product Surveillance Registry. (February 2020) - Stearns, Lisa M.; Abd-Elsayed, Alaa; Perruchoud, Christophe; Spencer, Robert; Hammond, Krisstin; Stromberg, Katherine; Weaver, Todd
Abstract : BACKGROUND: The safety and efficacy of intrathecal drug delivery systems (IDDSs) for the treatment of cancer-related pain have been demonstrated in randomized controlled clinical trials (RCTs). Despite positive evidence for this therapy, IDDS remains underutilized to treat cancer pain. Real-world registry data augment existing safety and effectiveness data and are presented here to broaden awareness of this therapeutic option, needed for adequate cancer-related pain treatment, and as a viable tool addressing concerns with systemic opioid use. METHODS: This prospective, long-term, multicenter (United States, Western Europe, and Latin America) registry started in 2003 to monitor the performance of SynchroMed Infusion Systems. Patient-reported outcomes were added in 2013. Before data acquisition, all sites obtained Ethics Committee/Institutional Review Board approval and written patient consent. The study was registered (NCT01524276 at clinicaltrials.gov) before patients were enrolled. Patients who provided informed consent were enrolled in the registry at initial IDDS implant or replacement. RESULTS: Through July 2017, 1403 patients with cancer pain were enrolled and implanted. The average (minimum/maximum) age of patients was 59 years (13/93 years), with 56.6% female. The most frequent cancer types were lung, breast, colon/rectal, pancreatic, and prostate. The majority of patients whose registry follow-up ended (87%; 1141/1311) were followed through death, with 4.3% (n = 57) exiting due to device explant or therapy discontinuation; the remaining 113 (8.6%) discontinued for reasons such as transfer of care, lost to follow-up, and site closure. Pain scores within the cohort of patients providing baseline and follow-up data improved significantly at 6 ( P = .0007; n = 103) and 12 ( P = .0026; n = 55) months compared to baseline, with EuroQol with 5 dimensions (EuroQol-5D) scores showing significant improvement at 6 months ( P = .0016; n = 41). Infection requiring surgical intervention (IDDS explant, replacement, pocket revision, irrigation and debridement, etc) was reported in 3.2% of patients. CONCLUSIONS: Adequate and improved pain control in patients with cancer, even in advanced stages, with concurrent quality of life maintenance is attainable. Results from this large-scale, multicenter, single-group cohort supplement existing RCT data that support IDDS as a safe and effective therapeutic option with a positive benefit–risk ratio in the treatment of cancer pain.